The concept of Argumentation for Aristotle - Bassal , Mohamad; Al-Oksh, Osamah (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
Studies and research about rhetoric have varied concerning the definition of rhetoric, but most of them look at rhetoric from on side only. Rhetoric was classified as being a kind of research concerned with the art of persuasion in its techniques, means and components. But it is certain that the political and social conditions of the greak life, led these philosophical studies and linguistic research especially, rhetoric. This made Aristotle divide rhetoric into three sections. The research delt with two main titles, the first one was Rhetoric according to Aristotle. It combines between mans ability to speak and express on one hand becavse man is a speaker and expressor who naturally looks for persuasion. In his speech, he tries to convince as many people as possible. To do this, he uses many instinctive means. Aristotle was concerned with rhetoric due to its mental and psychological sides. He tried to find a kind of balance between the means of persuasion and means of influence. He made convincing help infuencing. He diffentiated between kinds of proofs, the made proofs and the non made proofs. The other ones were the base of the rhetoric structure for Aristotle. The argumentative linguistic text is different from other texts that it builds an interactive structure based on some means that aim to persuade and affect the recipient.